Installation art of Dies Natalis as the Visual Identity of the Institute of Informatics and Business Darmajaya - Desiana Muryasari; Widarta; Muhammad Reza (PT FORMOSA CENDEKIA GLOBAL, 2024)
Campus promotion played an important role in establishing the positive image of the institutions. Visual media could be utilized to convey emotionally appealing messages, fostering a deep connection with the audience. This research centered on the campus of the Institute of Informatics and Business Darmajaya. The crafted artwork took the form of an installation encompassing the visual identity and philosophy of the campus, curated for the 26th Anniversary celebration (Dies Natalis) with dimensions measuring 1 x 1 x 1.8 meters. This study applied the 5W+1H as a research method, addressing the What, Who, Where, When, Why, and How questions. The distinctive form and layout of this artistic creation served as pivotal factors in rendering it an effective promotional medium. This unconventional installation art had the potential capacity to capture attention and leave a lasting impression on the targeted audience, especially prospective students